Conflict between Trees and Infrastructures in the Main Campus ofState University ofPadang - Rahman, Natasya Aulia; Kardiman, Reki; Roza, Sri Yenica (Bioscience, 2024)
Infrastructure is major supporting factor development a state and trees are planted throughoutthe infrastructure for the green aspect, which then promotes a conflict. Conflicts defined as tree growth atadjacent infrastructure,growth of roots causing a damages as in the main campus of State University ofPadang. This study to investigate the conflict between trees and infrastructure in the main campus of StateUniversityofPadang.Treespecies,diameter,size,canopy,distancetreetoinfrastructure,numberinfrastructureandtypeinfrastructureweresampledfrom195treesconflictandnotconflict.Alltreesbelongingto 12 species diameterfrom 26,75 cmto 114,01 cm(58,8392 cm onaverage), and canopyfrom300 m² to 825 m² (555,7692 m² on average). Trees planted to concrete by 71%, 33% conflicted, paving blockby 21%, 12% conflicted, and 8% to asphalt with 55% conflicted. Conflicted trees varied species but mostlyplanted <1 m from infrastructures, tended to larger diameter and narrow canopy cover. This study showedthere is 50% risk infrastucture damage planted close and tree species with lower potential conflict prioritizedforshade treesacrossinfrastructure.